The Role of Santri in Encouraging Business, Science, and Technology Innovation in Islamic Boarding Schools: Challenges and Opportunities - Herlina; Ernawati; Solikul Hadi (Proceeding of International Conference on Islamic Boarding School, 2025)
This study aims to analyze the role of santri (Islamic boarding school students) as agents of change in business innovation, science, and technology within pesantren (Islamic boarding schools). The research also explores the entrepreneurial potential of santri in the context of pesantren education and identifies the gap between theory and practice in the development of entrepreneurial and technological skills. The methodology used is a literature review, collecting and analyzing various literatures related to entrepreneurship, technology, and the role of santri in pesantren education. The findings show that santri have great potential to drive innovation in entrepreneurship and technology. However, there are major challenges such as the lack of a structured entrepreneurship curriculum and limited integration of technology in pesantren education. Therefore, it is crucial to address these challenges by enhancing technology infrastructure, providing teacher training, and aligning technology with educational goals to create a more inclusive and innovative learning environment.